2001
DOI: 10.1007/s11663-001-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and control of solidification of molten metal flows

Abstract: A solidified layer on the inside of a cooled flow channel can be used to control the flow rate of molten material through that channel. This concept can be used for flow rate control of molten furnace products in the metallurgical industry. In this study, internal solidification of molten metal flows has been modeled mathematically for both steady-state and dynamic cases. The model predicted solidified layer thickness and metal flow rate. Experimental verification of the mathematical model was obtained using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…[73][74][75][76] Nevertheless, the effect of flow dynamics on heat transfer has been analysed considerably less, 8,[77][78][79] while their combined influence on solidification is a relatively new topic. 8,80,81) Despite the extensive research on these phenomena, their effects on lubrication have been rarely addressed or even analysed in the context of defect formation during casting. This is possibly due to the fact that the slag phase has not been included in the calculations.…”
Section: Effect Of Flow Dynamics Heat Transfer and Solidificationmentioning
confidence: 99%
“…[73][74][75][76] Nevertheless, the effect of flow dynamics on heat transfer has been analysed considerably less, 8,[77][78][79] while their combined influence on solidification is a relatively new topic. 8,80,81) Despite the extensive research on these phenomena, their effects on lubrication have been rarely addressed or even analysed in the context of defect formation during casting. This is possibly due to the fact that the slag phase has not been included in the calculations.…”
Section: Effect Of Flow Dynamics Heat Transfer and Solidificationmentioning
confidence: 99%
“…It is reported that the growth of the solidified layer is strongly influenced by the superheat, the Rayleigh number and the axial position. The internal solidification of molten metal flows has been mathematically modeled for both steady and transient cases in [13]. The model predicts the solidified layer thickness and the metal flow rate, and an experimental verification of the mathematical model is reported using molten tin.…”
Section: Introductionmentioning
confidence: 99%